1999
DOI: 10.1046/j.1463-5224.1999.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optisol‐GS and neomycin‐polymyxin B‐gramicidin ophthalmic solution for corneal storage in the dog

Abstract: The objective of the research was to compare the efficacy of Optisol-GS (OGS, Bausch & Lomb Surgical, Irvine, CA, USA) with triple antibiotic ophthalmic solution (neomycin-polymyxin B-gramicidin, NPG; Bausch & Lomb, Tampa, FL, USA) in preserving the viability of corneal endothelial cells. The study subjects were thirty young to middle-aged dogs with no gross corneal pathology that had been euthanized by pentobarbital overdose for reasons unrelated to this project. Corneal tissues were harvested, analyzed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…(1991) in humans 12 and Andrew et al . (1999) in dogs 31 . After 5 days of storage, there was no evidence of cell loss in the endothelial cell layer, as assessed by light and scanning electron microscopy, although normal hexagonal shape had been lost in some cells.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…(1991) in humans 12 and Andrew et al . (1999) in dogs 31 . After 5 days of storage, there was no evidence of cell loss in the endothelial cell layer, as assessed by light and scanning electron microscopy, although normal hexagonal shape had been lost in some cells.…”
Section: Discussionmentioning
confidence: 83%
“…(1999) in dogs. 31 After 5 days of storage, there was no evidence of cell loss in the endothelial cell layer, as assessed by light and scanning electron microscopy, although normal hexagonal shape had been lost in some cells. In addition, a decrease in cell density, accompanied by cell hypertrophy was observed, which indicated that individual cells had died and been eliminated.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Analysis of healthy canine corneal endothelium using 0.2% alizarin red allowed clear identification of cell borders and was possible to identify and to evaluate the number of sides of each endothelial cell. Previous experiments with the use of alizarin red in different concentrations and exposition times have been performed (ANDREW et al, 1999;PARK et al 2012;FAGANELLO et al, 2016). Dual staining of corneal endothelium with vital dyes, using 0.2% alizarin red and 0.25% trypan blue, is the most frequently used technique for determining nonviable and viable cells in areas where cells cannot be identified with specular microscopy.…”
Section: Discussionmentioning
confidence: 99%